Method for preparing high-stability perovskite quantum dots by using organosilicon polymer
By introducing functional groups of silicone polymers on the surface of perovskite quantum dots, the problem of instability of perovskite quantum dots in high temperature and high humidity environments is solved, and its stability and optical properties are significantly improved.
Patent Information
- Application Number
- CN202411716728.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
AI Technical Summary
The existing perovskite quantum dots are unstable under conditions such as high temperature, high humidity and polar solvents, resulting in a degradation of optical properties.
Silicone polymers are used to react with perovskite quantum dot surfaces and introduce a variety of functional groups (such as thiol, amino, carboxyl and trifluoropropyl) to improve the stability of perovskite quantum dots through coordination.
It effectively improves the stability of perovskite quantum dots and ensures that their optical performance is maintained in high temperature and high humidity environments.
Smart Images

Figure CN119505873A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fluorescent materials, and in particular to a method for preparing high-stability perovskite quantum dots by using organosilicon polymers. Background Art
[0002] Perovskite quantum dots are a kind of semiconductor material with advantages such as high photoluminescence quantum yield, narrow emission bandwidth, tunable band gap and low cost. Therefore, perovskite quantum dots have great application prospects in light-emitting diodes, solar cells and photodetectors. However, due to the ionic crystal properties and low formation energy of perovskite quantum dots, perovskite quantum dots are very unstable under conditions such as high humidity, high temperature and polar solvents. This is mainly due to the weak binding ability of traditional monodentate ligands (oleic acid and oleylamine) to the surface of perovskite quantum dots. The ligands are easily detached under high temperature or high humidity environment, causing the agglomeration of perovskite quantum dots, which seriously affects their optical properties. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing high-stability perovskite quantum dots using organic silicon polymers in view of the deficiencies in the prior art, thereby overcoming the problem of poor stability of the existing perovskite quantum dots.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0005] A method for preparing high-stability perovskite quantum dots using organosilicon polymers comprises the following steps:
[0006] (1) mixing cesium carbonate, an organic acid and an octadecene solvent to prepare a precursor solution A;
[0007] (2) Mixing lead halide, octadecene solvent, organic acid ligand and organic amine ligand to prepare precursor solution B;
[0008] (3) adding precursor solution A to precursor solution B to react and obtain perovskite quantum dots;
[0009] (4) dispersing the perovskite quantum dots in a solvent, adding an organosilicon polymer to react under stirring conditions, and obtaining the organosilicon polymer-passivated perovskite quantum dots.
[0010] Furthermore, the organosilicon polymer is selected from at least one of mercaptopropyl polysiloxane, trifluoropropyl polysiloxane, amino polysiloxane and carboxyl polysiloxane.
[0011] Preferably, in the organosilicon polymer, the content of the functional groups mercapto, trifluoropropyl, amino and carboxyl accounts for 5-80% of the total number of polysiloxane chain segments, preferably 30-80%; and the molecular weight of the organosilicon polymer is 200-20,000.
[0012] Furthermore, the mass ratio of the perovskite quantum dots to the organosilicon polymer is 1:(0.1-10).
[0013] Furthermore, in the precursor solution A of step (1), the concentration of cesium carbonate is 0.0102-0.0612 g / mL, and the volume ratio of the organic acid to the solvent is 1:(4-20).
[0014] Furthermore, in the precursor solution A of step (1), the organic acid is at least one of fatty acids having 1 to 18 carbon atoms, preferably oleic acid.
[0015] Furthermore, in the step (1), the step of preparing the precursor solution A is as follows: in a vacuum environment, cesium carbonate, an organic acid and octadecene are mixed, heated at 100 to 150° C. for 30 to 90 minutes, and then a protective gas is introduced, and the temperature is raised to 150 to 200° C. and kept warm until the solution is completely reacted, thereby obtaining the precursor solution A.
[0016] Furthermore, in the precursor solution B of step (2), the concentration of the lead halide is 0.0418-1.730 g / mL; the volume ratio of the organic acid ligand to the solvent is 1:(5-30), the volume ratio of the organic amine ligand to the solvent is 1:(5-30); the volume ratio of the organic acid ligand to the organic amine ligand is 1:(0.1-10).
[0017] Furthermore, in the precursor solution B of step (2), the lead halide is selected from at least one of lead chloride, lead bromide and lead iodide; the organic acid ligand is selected from at least one of organic carboxylic acid ligands and organic phosphoric acid ligands, preferably a fatty acid with a carbon number of 10 to 18, and more preferably oleic acid; the organic amine ligand is selected from at least one of organic primary amine ligands, organic secondary amine ligands and organic tertiary amine ligands, preferably a fatty amine with a carbon number of 10 to 18, and preferably oleylamine; and the protective gas is selected from at least one of nitrogen, helium, argon and neon.
[0018] Furthermore, in step (2), the step of preparing the precursor solution B is as follows: under vacuum conditions, lead halide, octadecene solvent, organic acid ligand and organic amine ligand are mixed, and heated to react at 80 to 130° C. for 30 to 90 minutes; then, a protective gas is introduced and the temperature is raised to 150 to 200° C. to obtain the precursor solution B.
[0019] Furthermore, in step (3), the reaction time is 5 to 30 seconds.
[0020] Furthermore, the step (3) further comprises: cooling with ice water after the reaction is completed, centrifuging at 3000-12000 r / min, removing the supernatant, and collecting the precipitate to obtain the perovskite quantum dots.
[0021] Furthermore, in step (4), the solvent is n-hexane and / or toluene; and the mass volume ratio of the perovskite quantum dots to the solvent is 1:(1-30).
[0022] Furthermore, in step (4), the reaction time is 5 to 30 minutes.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention provides a method for preparing high-stability perovskite quantum dots using organosilicon polymers. The method synthesizes perovskite quantum dots under high temperature and protective gas environment conditions, effectively ensuring the repeatability of perovskite quantum dot synthesis.
[0025] 2. The method of preparing high-stability perovskite quantum dots using organosilicon polymers of the present invention, wherein a variety of functional groups of organosilicon polymers are introduced into the perovskite quantum dots, wherein carboxyl, amino, trifluoropropyl and thiol functional groups have strong coordination effects with the surface of perovskite nanocrystals, thereby effectively improving the stability of perovskite nanocrystals. However, too few functional group ratios have poor treatment effects, and too many functional group ratios have destructive effects on the crystal structure of perovskite nanocrystals. Selecting an appropriate molecular weight range is more conducive to the coordination of functional groups and perovskite surfaces. When the molecular weight is too high, the ligand itself has poor solubility and cannot achieve effective surface passivation, while too low a molecular weight will make the solubility of perovskite nanocrystals poor. The present invention regulates the molecular weight of the organosilicon polymer, the ratio of the coordinated functional groups and the types of functional groups, so that it has excellent adaptability and compatibility, thereby effectively improving the stability of perovskite quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the X-ray diffraction spectrum of the perovskite quantum dots after passivation with the organosilicon polymer in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is only an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the invention of the present invention based on the disclosed content, and they should also fall within the scope of the present invention.
[0028] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.
[0029] Example 1
[0030] A method for preparing high-stability perovskite quantum dots using organosilicon polymers comprises the following steps:
[0031] (1) 3.256 g of cesium carbonate, 12 mL of oleic acid and 120 mL of octadecene were weighed into a 250 mL three-necked flask, heated to 120° C., and maintained under vacuum for 1 h; then nitrogen was introduced and the temperature was raised to 150° C. until the cesium carbonate was completely dissolved, thereby obtaining a precursor solution A;
[0032] (2) Weigh 1.41 g of lead bromide, 10 mL of oleic acid, 10 mL of oleylamine and 100 mL of octadecene solvent in a 250 mL three-necked flask, heat to 120° C., and maintain under vacuum for 1 h. After vacuuming, introduce nitrogen and heat to 160° C. to obtain a precursor solution B;
[0033] (3) 8 mL of precursor solution A was added to precursor solution B, and after reacting for 15 seconds, the mixture was placed in ice water and cooled to room temperature, and then centrifuged at 8000 r / min for 10 minutes, the supernatant was removed, and the precipitate was collected to obtain perovskite quantum dots;
[0034] (4) The perovskite quantum dots were dissolved in 10 mL of toluene to obtain a perovskite quantum dot solution. Under stirring, 100 μL of mercaptopropyl polysiloxane (mercaptopropyl accounts for 30% of the total number of chain segments and the number average molecular weight is 3200) was added to the perovskite quantum dot solution. After reacting for 20 minutes, the solution was centrifuged at 5000 r / min for 10 minutes, the supernatant was discarded, and the precipitate was collected to obtain perovskite quantum dots passivated with mercaptopropyl polysiloxane.
[0035] Example 2
[0036] Another method for preparing high-stability perovskite quantum dots using organosilicon polymers comprises the following steps:
[0037] (1) 3.256 g of cesium carbonate, 12 mL of oleic acid and 120 mL of octadecene were weighed into a 250 mL three-necked flask, heated to 120° C., and maintained under vacuum for 1 h; then nitrogen was introduced and the temperature was raised to 150° C. until the cesium carbonate was completely dissolved, thereby obtaining a precursor solution A;
[0038] (2) Weigh 1.41 g of lead bromide, 10 mL of oleic acid, 10 mL of oleylamine and 100 mL of octadecene solvent in a 250 mL three-necked flask, heat to 120° C., and maintain under vacuum for 1 h. After vacuuming, introduce nitrogen and heat to 160° C. to obtain a precursor solution B;
[0039] (3) 8 mL of precursor solution A was added to precursor solution B, and after reacting for 15 seconds, the mixture was placed in ice water and cooled to room temperature, and then centrifuged at 8000 r / min for 10 minutes, the supernatant was removed, and the precipitate was collected to obtain perovskite quantum dots;
[0040] (4) The perovskite quantum dots were dissolved in 10 mL of toluene to obtain a perovskite quantum dot solution. Under stirring, 100 μL of carboxyl polysiloxane (carboxyl groups accounted for 30% of the total number of chain segments and the number average molecular weight was 1300) was added to the perovskite quantum dot solution. After reacting for 20 minutes, the solution was centrifuged at 5000 r / min for 10 minutes, the supernatant was discarded, and the precipitate was collected to obtain the perovskite quantum dots passivated with carboxyl polysiloxane.
[0041] Example 3
[0042] Another method for preparing high-stability perovskite quantum dots using organosilicon polymers comprises the following steps:
[0043] (1) 3.256 g of cesium carbonate, 12 mL of oleic acid and 120 mL of octadecene were weighed into a 250 mL three-necked flask, heated to 120° C., and maintained under vacuum for 1 h; then nitrogen was introduced and the temperature was raised to 150° C. until the cesium carbonate was completely dissolved, thereby obtaining a precursor solution A;
[0044] (2) Weigh 1.41 g of lead bromide, 10 mL of oleic acid, 10 mL of oleylamine and 100 mL of octadecene solvent in a 250 mL three-necked flask, heat to 120° C., and maintain under vacuum for 1 h. After vacuuming, introduce nitrogen and heat to 160° C. to obtain a precursor solution B;
[0045] (3) 8 mL of precursor solution A was added to precursor solution B, and after reacting for 15 seconds, the mixture was placed in ice water and cooled to room temperature, and then centrifuged at 8000 r / min for 10 minutes, the supernatant was removed, and the precipitate was collected to obtain perovskite quantum dots;
[0046] (4) The perovskite quantum dots were dissolved in 10 mL of toluene to obtain a perovskite quantum dot solution. Under stirring, 100 μL of trifluoropropyl polysiloxane (trifluoropropyl accounts for 30% of the total number of chain segments and the number average molecular weight is 2100) was added to the perovskite quantum dot solution. After reacting for 20 minutes, the solution was centrifuged at 5000 r / min for 10 minutes, the supernatant was discarded, and the precipitate was collected to obtain trifluoropropyl polysiloxane-passivated perovskite quantum dots.
[0047] Example 4
[0048] Another method for preparing high-stability perovskite quantum dots using organosilicon polymers comprises the following steps:
[0049] (1) 3.256 g of cesium carbonate, 12 mL of oleic acid and 120 mL of octadecene were weighed into a 250 mL three-necked flask, heated to 120° C., and maintained under vacuum for 1 h; then nitrogen was introduced and the temperature was raised to 150° C. until the cesium carbonate was completely dissolved, thereby obtaining a precursor solution A;
[0050] (2) Weigh 1.41 g of lead bromide, 10 mL of oleic acid, 10 mL of oleylamine and 100 mL of octadecene solvent in a 250 mL three-necked flask, heat to 120° C., and maintain under vacuum for 1 h. After vacuuming, introduce nitrogen and heat to 160° C. to obtain a precursor solution B;
[0051] (3) 8 mL of precursor solution A was added to precursor solution B, and after reacting for 15 seconds, the mixture was placed in ice water and cooled to room temperature, and then centrifuged at 8000 r / min for 10 minutes, the supernatant was removed, and the precipitate was collected to obtain perovskite quantum dots;
[0052] (4) The perovskite quantum dots were dissolved in 10 mL of toluene to obtain a perovskite quantum dot solution. Under stirring, 100 μL of aminopolysiloxane (amino groups accounted for 30% of the total number of chain segments and the number average molecular weight was 2100) was added to the perovskite quantum dot solution. After reacting for 20 minutes, the solution was centrifuged at 5000 r / min for 10 minutes, the supernatant was discarded, and the precipitate was collected to obtain aminopolysiloxane-passivated perovskite quantum dots.
[0053] Example 5
[0054] The difference between this embodiment and embodiment 3 is that the trifluoropropyl groups of the trifluoropropyl polysiloxane in step (4) account for 80% of the total number of chain segments and the number average molecular weight is 2100.
[0055] Example 6
[0056] The difference between this embodiment and embodiment 3 is that the trifluoropropyl groups of the trifluoropropyl polysiloxane in step (4) account for 3% of the total number of chain segments and the number average molecular weight is 2100.
[0057] Example 7
[0058] The difference between this embodiment and embodiment 3 is that the trifluoropropyl groups of the trifluoropropyl polysiloxane in step (4) account for 85% of the total number of chain segments and the number average molecular weight is 2100.
[0059] Example 8
[0060] The difference between this embodiment and embodiment 3 is that the trifluoropropyl groups of the trifluoropropyl polysiloxane in step (4) account for 30% of the total number of chain segments and the number average molecular weight is 20,000.
[0061] Example 9
[0062] The difference between this embodiment and embodiment 3 is that in step (4), the trifluoropropyl groups of the trifluoropropyl polysiloxane account for 30% of the total number of chain segments, and the number average molecular weight is 180.
[0063] Example 10
[0064] The difference between this embodiment and embodiment 3 is that the trifluoropropyl groups of the trifluoropropyl polysiloxane in step (4) account for 30% of the total number of chain segments and the number average molecular weight is 25,000.
[0065] Comparative Example 1
[0066] The difference between this comparative example and Example 1 is that step (4) includes 100 μL of polydimethylsiloxane (number average molecular weight is 2100).
[0067] Comparative Example 2
[0068] The difference between this comparative example and Example 3 is that 5 mL of trifluoropropyl polysiloxane (trifluoropropyl accounts for 30% of the total number of chain segments and the number average molecular weight is 2100) is added in step (4).
[0069] Comparative Example 3
[0070] A method for preparing perovskite quantum dots comprises the following steps:
[0071] (1) 3.256 g of cesium carbonate, 12 mL of oleic acid and 120 mL of octadecene were weighed into a 250 mL three-necked flask, heated to 120° C., and maintained under vacuum for 1 h; then nitrogen was introduced and the temperature was raised to 150° C. until the cesium carbonate was completely dissolved, thereby obtaining a precursor solution A;
[0072] (2) Weigh 1.41 g of lead bromide, 10 mL of oleic acid, 10 mL of oleylamine and 100 mL of octadecene solvent in a 250 mL three-necked flask, heat to 120° C., and maintain under vacuum for 1 h. After vacuuming, introduce nitrogen and heat to 160° C. to obtain a precursor solution B;
[0073] (3) Take 8 mL of precursor solution A and add it to precursor solution B. After reacting for 15 seconds, place it in ice water to cool to room temperature, and then centrifuge it at 8000 r / min for 10 minutes. Remove the supernatant and collect the precipitate to obtain perovskite quantum dots.
[0074] Test example
[0075] Fluorescence tests were performed on the perovskite quantum dots prepared in the above examples and comparative examples, and the perovskite quantum dots passivated with organosilicon polymers. The results are shown in Tables 1-3 below.
[0076] Table 1. Fluorescence intensity at different time in water
[0077] Group initial 12h 24h 48h Example 1 100% 95% 85% 74% Example 2 100% 91% 81% 71% Example 3 100% 92% 86% 76% Example 4 100% 94% 82% 73% Example 5 100% 96% 86% 77% Example 6 100% 62% 41% 23% Example 7 100% 48% 31% 19% Example 8 100% 93% 82% 72% Example 9 100% 58% 39% 24% Example 10 100% 57% 44% 29% Comparative Example 1 100% 27% 11% 6% Comparative Example 2 100% 34% 13% 9% Comparative Example 3 100% 19% 8% 3%
[0078] Table 2. Fluorescence intensity at different times under 90℃
[0079]
[0080]
[0081] Table 3. Fluorescence intensity at different times under 90℃ and 70% relative humidity
[0082] Group initial 12h 24h 48h Example 1 100% 74% 63% 51% Example 2 100% 75% 61% 49% Example 3 100% 70% 62% 53% Example 4 100% 76% 65% 57% Example 5 100% 74% 61% 52% Example 6 100% 48% 39% 22% Example 7 100% 44% 25% 15% Example 8 100% 71% 64% 52% Example 9 100% 49% 37% 22% Example 10 100% 48% 35% 18% Comparative Example 1 100% 15% 9% 4% Comparative Example 2 100% 23% 14% 7% Comparative Example 3 100% 11% 5% 2%
[0083] As shown in the table above, compared with Comparative Example 3, the fluorescence intensity of the perovskite quantum dots passivated by the organosilicon polymer obtained in Examples 1-4 under high temperature, high humidity and high temperature and high humidity conditions decreased relatively less, indicating that compared with the unmodified perovskite quantum dots, the perovskite quantum dots passivated by the organosilicon polymer modified by the method provided by the present invention have good stability. It can also be seen that the molecular weight, the ratio of the coordination functional groups and the types of the functional groups of the organosilicon polymer have a great influence on the stability of the perovskite quantum dots. The present invention regulates the molecular weight, the ratio of the coordination functional groups and the types of the functional groups of the organosilicon polymer to make it have excellent adaptability and compatibility, thereby effectively improving the stability of the perovskite quantum dots.
[0084] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing high-stability perovskite quantum dots using organosilicon polymers, characterized in that: The following steps are involved: (1) mixing cesium carbonate, an organic acid and an octadecene solvent to prepare a precursor solution A; (2) mixing lead halide, octadecene solvent, organic acid ligand and organic amine ligand to prepare precursor solution B; (3) adding precursor solution A to precursor solution B to react and obtain perovskite quantum dots; (4) dispersing the perovskite quantum dots in a solvent, adding an organosilicon polymer to react under stirring conditions, and obtaining the organosilicon polymer-passivated perovskite quantum dots.
2. The method for preparing high-stability perovskite quantum dots using organosilicon polymers according to claim 1, characterized in that: In step (4), the organosilicon polymer is selected from at least one of mercaptopropyl polysiloxane, trifluoropropyl polysiloxane, amino polysiloxane and carboxyl polysiloxane.
3. The method for preparing high-stability perovskite quantum dots using organosilicon polymers according to claim 2, characterized in that: In the organic silicon polymer, the content of the functional groups of mercapto, trifluoropropyl, amino and carboxyl accounts for 1 to 80% of the total number of polysiloxane chain segments; and the molecular weight of the organic silicon polymer is 200 to 20,000.
4. The method for preparing high-stability perovskite quantum dots using organosilicon polymers according to claim 1, characterized in that: In the precursor solution A of step (1), the concentration of cesium carbonate is 0.0102-0.0612 g / mL, and the volume ratio of the organic acid to the solvent is 1:(4-20).
5. The method for preparing high-stability perovskite quantum dots using organosilicon polymers according to claim 1, characterized in that: In the precursor solution A of step (1), the organic acid is at least one of fatty acids having 1 to 18 carbon atoms, preferably oleic acid.
6. The method for preparing high-stability perovskite quantum dots using organosilicon polymers according to claim 1, characterized in that: In the precursor solution B of the step (2), the concentration of the lead halide is 0.0418-1.730 g / mL; the volume ratio of the organic acid ligand to the solvent is 1:(5-30), the volume ratio of the organic amine ligand to the solvent is 1:(5-30); the volume ratio of the organic acid ligand to the organic amine ligand is 1:(0.1-10).
7. The method for preparing high-stability perovskite quantum dots using organosilicon polymers according to claim 1, characterized in that: In the precursor solution B of step (2), the lead halide is selected from at least one of lead chloride, lead bromide and lead iodide; the organic acid ligand is selected from at least one of an organic carboxylic acid ligand and an organic phosphoric acid ligand; and the organic amine ligand is selected from at least one of an organic primary amine ligand, an organic secondary amine ligand and an organic tertiary amine ligand.
8. The method for preparing high-stability perovskite quantum dots using organosilicon polymers according to claim 1, characterized in that: In step (2), the step of preparing the precursor solution B is as follows: under vacuum conditions, lead halide, octadecene solvent, organic acid ligand and organic amine ligand are mixed, and heated to react at 80 to 130° C. for 30 to 90 minutes; then a protective gas is introduced and the temperature is raised to 150 to 200° C. to obtain the precursor solution B.
9. The method for preparing high-stability perovskite quantum dots using organosilicon polymers according to claim 1, characterized in that: The step (3) further comprises: cooling with ice water after the reaction is completed, centrifuging at 3000-12000 r / min, removing the supernatant, and collecting the precipitate to obtain the perovskite quantum dots.
10. The method for preparing high-stability perovskite quantum dots using organosilicon polymers according to claim 1, characterized in that: The mass ratio of the perovskite quantum dots to the organosilicon polymer is 1:(0.1-10).
Citation Information
Patent Citations
Method for synthesizing silicon dioxide cladded organic-inorganic perovskite structure quantum dot and application of quantum dot synthesized by method
CN107446572A
Red and green light perovskite quantum dot stable fluorescent powder based on SiO2 coating and preparation
CN110872510A
Perovskite microsphere, mixed-color optical conversion film, and displayer
CN110922961A
Method for preparing high-performance perovskite quantum dots based on sulfydryl silane ligand exchange
CN111088045A
Method for preparing cesium-lead halide perovskite quantum dots based on in-situ mercaptosilane passivation
CN112251221A